Cell division suppression in the Bacillus subtilis div IC-A1 minicell-producing mutant. - Mendelson, N H (1975)
Growth and division patterns of Bacillus subtilis wild-type (div IV-A1+) and minicell-producing mutant (div IV-A1) clones were studied after spore germination during microcolony development in chambers that facilitate continuous observation with a phase contrast microscope. Data obtained from 13 div IV-A1+ clones were used to derive the equation DE equals [(mum minus 17.6)/8.8], which expresses the relationship of cell divisions present in clones of various lengths. This equation was used to determine the number of divisions expected in div IV-A1 clones if the mutant clones were able to divide as often as wild-type clones. The observed number of divisions present in mutant clones was found to be only 25.27% of the number expected on the basis of this equation. Although individual div IV-A1 clones varied in the percentage of division equivalents expressed, there appeared to be no correlation between the overall clone growth rate and the number of divisions expressed. Culturing div IV-A1+ and div IV-A1 clones together in the same growth chamber revealed that there were no diffusible interactions influencing the division phenotypes of either mutant or wild-type cells. At later stages of growth, mixed microcolonies containing cells of both genotypes were formed. A length analysis of individual cells in these populations indicated that the relative division suppression of mutant compared with wild-type cells characteristic of the initial stages of clone development was maintained. It is likely, therefore, that the excessive length of minicell-producing cells (div IV-A1) is a reflection primarily of division suppression in the mutant and not simply of mislocation of division along cell length.